The Ideal Career Woman from The Al- Qur'an Perspective - Rosyidah, Ainur (JURNAL ISLAM NUSANTARA, 2023)
This research aims to analyze the interpretation of the verses of the Qur'an about the ideal career woman in Surah An-Nahl/16:97 and Al-Qashash/28:23-25, as well as explain the description of the ideal career woman from the perspective of al-Koran. This research uses a qualitative descriptive approach with literature study and interpretation of the Koran, highlighting the need for an in-depth understanding of career women in Islam. The results of this research, based on the interpretation of the verses of the Koran, suggest that ideal career women are those who do good and halal work, avoid work that can hurt themselves and the environment, and are good at protecting themselves from sinful acts. They are also advised to dress modestly and cover their private parts by the teachings of the Islamic religion, which emphasizes modesty and self-protection. This is expected to clarify the Koran's view regarding the ideal career woman, providing a strong theoretical foundation for Muslim women who want to develop their careers in the public sphere.